A Profile of Social Skills of Students in Learning Physics through Problem-Posing Approach - Syafrilianto Syafrilianto; Ahmad Nizar Rangkuti (Universitas Lambung Mangkurat, 2020)
This article describes senior high school students' social skills in learning physics by applying the problem-posing approach. This study conducted by implementing a pre-experimental method of the One-Shot Case Study. The samples of this study were 38 students from XII Science class who chosen from a population of 240 students at grade X, XI, and XII at one of the senior high schools in Tapanuli Selatan. The data of students' social skills collected through observation sheets of social skills with five aspects of indicators, namely being consistent with doing tasks, encouraging participation, taking turns and sharing tasks, listening actively, and asking questions. The data analyzed by calculating the average score of students social from each indicator. The score of each indicator of the students' social skills was varied for every meeting, ranging from very high, high, moderate, low to very low, and so was the number of students for each criterion of social skills on each meeting. The results concluded that the profile of social skills in learning physics through a problem-posing approach revealed various levels of mastery of the students' social skills. The variety could be observed from the ability of social skills on each indicator and the number of students for each criterion of social skills in each meeting.